(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
This paper suggests that literature has important consequences for the theoretical practice of island studies, not least because literary documents illustrate the conceptualization of the islands in various historical and cultural perspectives. To this end, Amitav Ghosh’s The Hungry Tide (2004) is addressed. This novel aggressively theories core ideas of island studies. Set in the immense archipelago of the Ganges delta, the Hungry Tide tells the mostly forgotten tale of forced evacuation from Morichjhãpi Island in 1979. The liminal space of the Sundarbans, the tide nation, is an exceptional place to investigate the relationship of post-colonial geographies with identities. The portrayal of the watery maze (Ghosh, 2004 72) and storm-tossed reefs (Sundarbans, 2004 164) by Ghosh poses and answers issues that should be at the core of the crucial meta-discourse of island science.